Real-world disparities and ethical considerations with access to CFTR modulator drugs: Mind the gap! - Zampoli, M.; Morrow, B. M; Paul, G (Frontiers in Pharmacology, 2023)
The third Sustainable Development Goal (SDG), to ensure healthy lives and promote well-being for all at all ages, has particular relevance and implementation challenges amongst people living with rare diseases such as cystic fibrosis (CF). Although the treatment and projected outcome of CF has significantly improved with the advent of CF transmembrane conductance regulator protein modulator (CFTRm) therapy, there remains significant global inequality with regards to access to these life-saving and life-altering drugs. Elexacaftor, tezacaftor, and ivacaftor (ETI) triple combination therapy, first licensed in the United States in 2019, has rapidly become the standard of care for children aged 6 years and older in most high-income countries for individuals with CFTR variants responsive to ETI. Negotiated agreements for access to ETI are currently in place in North America,Europe, Israel ,Australia and New Zealand. However, less priority has been given to negotiate agreements for access to CFTRm in low-middle income countries(LMIC) with significant CF populations such as Central and South America, India, the Middle East, and Southern Africa. These countries and individuals living with CF are therefore effectively being left behind, in direct conflict with the stated principle of the 2030 SDGs. In this review, we highlight the current global inequity in access to CFTRm drugs and its impact on widening disparities between high-income countries and LMIC in CF outcomes and survival. We further discuss the reasons for this inequity and explore the ethical- and human rights-based principles and dilemmas that clinicians, families, governments, and healthcare funders must consider when prioritizing fair and affordable access to expensive CFTRm drugs. Lastly, we propose possible solutions to overcoming the barriers to accessing affordable CFTRm drugs in LMIC and illustrate with examples how access to drug therapies for other conditions have been successfully negotiated in LMIC through innovative partnerships between governments and pharmaceutical industries.